Study of Modern Nano Enhanced Techniques for Removal of Dyes and Metals. (25th May 2014) - Batool, Samavia; Akib, Shatirah; Ahmad, Mushtaq; Balkhair, Khaled S.; Ashraf, Muhammad Aqeel
Abstract : Industrial effluent often contains the significant amount of hexavalent chromium and synthetic dyes. The discharge of wastewater without proper treatment into water streams consequently enters the soil and disturbs the aquatic and terrestrial life. A range of wastewater treatment technologies have been proposed which can efficiently reduce both Cr(VI) and azo dyes simultaneously to less toxic form such as biodegradation, biosorption, adsorption, bioaccumulation, and nanotechnology. Rate of simultaneous reduction of Cr(VI) and azo dyes can be enhanced by combining different treatment techniques. Utilization of synergistic treatment is receiving much attention due to its enhanced efficiency to remove Cr(VI) and azo dye simultaneously. This review evaluates the removal methods for simultaneous removal of Cr(VI) and azo dyes by nanomicrobiology, surface engineered nanoparticles, and nanophotocatalyst. Sorption mechanism of biochar for heavy metals and organic contaminants is also discussed. Potential microbial strains capable of simultaneous removal of Cr(VI) and azo dyes have been summarized in some details as well.